Filariasis caused by nonperiodic form of Brugia malayi among school children in the settlement of Dayak indigenous people and transmigrants in East Kalimantan - FA Sudjadi FA Sudjadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1999)
Background: New filarial worm subspecies, i.e. nonperiodic form of Brugia malayi Lichtenstein, was recently reported from East Kalimantan in addition to the previously known subperiodic and periodic form of the species, which was endemic in some rural areas in Indonesia.Objectives: (1) To search new endemic areas of filariasis in the indigenous people and newcomers. (2) To know current status of the disease among schoolchildren in the study areas.Subjects: Schoolchildren in the settlement of Dayak indigenous people (Krayan and Kayungo villages) and transmigrants (Petung UPT: Girimukti and Petung villages), belonging to Long Ikis and Penajam subdistricts, the district of Pasir.Methods: Based on the microfilarial character of aperiodic, blood examinations by simple or concentration method on schoolchidren were carried out at day time within school hours in 1987/1988.Results: (1) Endemic areas of the B. malayi subspecies were discovered, not only in the villages where the schools were situated, but their vicinities as well, i.e. the school children's home villages. The other schoolchildren's home villages found as endemic areas were Jemparing, Nipaulo, Olung, Sepingan around the Dayak settlements and Lawe-lawe, Tanjung Jumlai, Salakloang, Tunan around the UPT of Petung. (2) Higher microfilaremia rates were found in schools in Krayan (26,0% or 52/200 children) and Kayungo (14,8% or 16/108 children). In the transmigrant settlement, although the concentration methods of examinations were adopted, lower microfilaremia rates were recorded such in schools in the villages of Girimukti (6,9% or 34/490 children) and Petung (3,5% or 33/950 children).Conclusions: Day-time blood survey at school was proved to be a simple method to discover endemic areas of the nonperiodic form of B. malayi in East Kalimantan.Key words: B.ma/ayi - nonperiodic form - daytime examinations - school children